Sensory quality and physicochemical properties of cassava roots as a function of technological management levels and harvest times (Research, Society and Development, 2021)
The management practices used by farmers in cassava crops and the relationship with the sensory quality and physicochemical characteristics of cassava roots are still incipient. The objective of this work was to evaluate the productivity, sensory quality and physicochemical properties of cassava roots at harvest times and technological management levels. The study was conducted in Santa Maria, Rio Grande do Sul, Brazil, and the management practices employed in the field experiment corresponded to low, medium and high technological levels used by farmers in southern Brazil. The cultivar “Vassourinha” was used and the roots were harvested in the sixth, the seventh, and the eighth month after planting. The productivity, the physicochemical composition of the roots (dry matter, protein, lipid, ash, total fiber, resistant starch, and total starch) were determined, and the sensory analysis of the roots was performed. Technological levels did not influence the root productivity and it increased with the delay in the harvest season. There was an increase in protein at the high technological level and the highest content of starch was found in the roots harvested in the seventh month. Sensory acceptance of the roots showed greater acceptability in the sixth and seventh months after planting, with roots of a high technological level being preferred. Based on the results, the influence of management practices in the nutritional composition of the roots represents an important aspect for assessing the potential of the roots to be consumed or used in industrial processes.